Analysis of the Implementation of Total Productive Maintenance (TPM) Using Overall Equipment Effectiveness (OEE) : (Case Study of PT. Pertamina Hulu Rokan Jambi Merang) - Sudirnanto; Amalia Ma’rifatul Maghfiroh; Rizky Stighfarrinata (Journal of Social Science and Economics, 2022)
Basically, the control of maintenance/maintenance can be determined according to business needs and operating conditions. However, changes may occur and require adjustment from time to time. So every part of the maintenance needs to organize the system effectively. In this regard, it is important for management to pay attention to analyzing the implementation of Total Productive Maintenance (TPM) on maintenance work. At the SKN Plant which is the Central Gas Plant there are several gas processing processes, one of which is the Amine System or CO2 Removal which functions to reduce the level of CO2 contained in gas production. In the Amine System or CO2 removal process there are several equipment to support the process One of these is the Amine Circulation Pump (SK 25 P 05 A/B) which runs continuously alternately unit A and unit B. To maintain the pump's performance, the company performs maintenance by implementing a Total Productive Maintenance (TPM) system. The extent to which the effectiveness of the implementation of the TPM system carried out by Pertamina Hulu Rokan Jambi Merang, the author will analyze using the Overall Equipment Effectiveness (OEE) approach to the Amine Circulation Pump (SK 25 P 05 A/B). The formulation of the problem in this research is the application of Total Productifities Maintenance (TPM) on the Amine Circulation Pump (SK 25 P 05 A/B) in the CO2 removal process (Amine System) using the Overall Equipment Effectiveness (OEE) approach with the aim of knowing the level of reliability of the pump. Amine Circulation (SK 25 P 05 A/B) in the CO2 removal process (Amine System) using the Overall Equipment Effectiveness (OEE) approach. The results of this study are the average Overral Equipment Effectiveness value at PT Pertamina Hulu Rokan Jambi Merang on the amine circulation pump engine SK 25 P05 A/B from January-December is 56.68%. Based on the analysis of Overall Equipment Effectiveness, the current maintenance system is not optimal because it is not in accordance with the standards set by JIPM of > 85%.